Doing More with Less: Innovation Input and Output in Family Firms - Duran, Patricio; Kammerlander, Nadine; van Essen, Marc; Zellweger, Thomas (Academy of Management Journal, 2016)
Family firms are often portrayed as an important yet conservative form of organization that is reluctant to invest in innovation; however, simultaneously, evidence has shown that family firms are flourishing and in fact constitute many of the world’s most innovative firms. Our study contributes to disentangling this puzzling effect. We argue that family firms—owing to the family’s high level of control over the firm, wealth concentration, and importance of nonfinancial goals—invest less in innovation but have an increased conversion rate of innovation input into output and, ultimately, a higher innovation output than nonfamily firms. Empirical evidence from a meta-analysis based on 108 primary studies from 42 countries supports our hypotheses. We further argue and empirically show that the observed effects are even stronger when the CEO of the family firm is a later-generation family member. However, when the CEO of the family firm is the firm’s founder, innovation input is higher and, contrary to our initial expectations, innovation output is lower than that in other firms. We further show that the family firm–innovation input–output relationships depend on country-level factors; namely, the level of minority shareholder protection and the education level of the workforce in the country.